Pengaruh Katekese Perkawinan Terhadap Kesiapan Emosional dan Mental Pasangan Calon Suami Istri dalam Membangun Rumah Tangga di Paroki Katedral Denpasar - Agustina Paschalia Elitawati Lamabelawa; Lidia Sandra (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Marriage is a sacred vocation that signifies a profound commitment between husband and wife, rooted in love and faith. Many couples, however, lack the emotional and mental readiness to navigate marital challenges. This study examines the impact of Pre-Marriage Catechesis (KPP) on the emotional and mental readiness of Catholic couples in the Holy Spirit Cathedral Parish, Denpasar. Using a pretest- posttest experimental design, data were collected from 89 participants (44 males, 45 females) in November 2024, utilizing the Sukoon Marriage Readiness Scale. Before KPP, participants were categorized as